(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article analyzes the dynamics of changes in the volume of services of the market “telecommunications” and its correlation with the introduction of information and communication technologies. The analysis of data from licensed activities of telecom operators indicates that the introduction of new technologies, their high efficiency and indispensability in the daily life of society, as well as affordable prices due to high competition, provides progress in the introduction of innovative digital technologies, which also affects the reduction of other less demanded services.